THE EFFECT OF THE APPLICATION OF POSITIVE PSYCHOLOGY ON THE DEVELOPMENT OF HUMAN RESOURCE PERFORMANCE AT PT MANDIRI ABADI PERMAI KOTA MEDAN - Liandra Khairunnisa; Hafiz Nurdiansyah (CV. Radja Publika, 2025)
This study aims to analyze the influence of the application of positive psychology on the development of human resource (HR) performance at PT Mandiri Abadi Permai Medan City. This study uses a quantitative approach with explanatory methods and simple linear regression analysis techniques. A sample of 92 respondents was selected through simple random sampling from a total population of 120 employees. The research instrument was in the form of a closed questionnaire with a Likert scale and tested for validity and reliability. The results of the study show that there is a positive and significant influence between positive psychology and human resource performance. A significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.398 showed that 39.8% of variations in HR performance could be explained by the application of positive psychology, while the rest were influenced by other factors. These findings are reinforced by Seligman's positive psychology theory and Luthans' concept of Psychological Capital, which emphasizes the importance of optimism, hope, and resilience in supporting work productivity. Thus, companies need to integrate positive psychology approaches in HR development strategies to create a healthy, adaptive, and productive work environment.